Revision of Neotropical aphrophorine spittlebugs, part 2: tribe Orthoraphini (Hemiptera, Cercopoidea) - Hamilton, K. G. Andrew (Zootaxa, 2013)
The tribe Orthoraphini is validated by diagnosis to include the new-world fauna of Orthorapha Westwood with 21 species from Brazil and 2 newly recorded from Bolivia, including 9 new species: boliviana from an unknown locality in Bolivia and decorata, inscripta, inflata, invidia, irregularis, oculata, sagittata and sphaerata from Brazil. There are also 10 new combinations from Lepyronia Amyot & Serville: bufo Walker, concinna Stål, frontalis Stål, fusconotata Stål, geminata Jacobi, obscurata Amyot & Serville, obliqua Jacobi, quadrimaculata Lallemand, rana Walker and subfasciata Amyot & Serville. Keys are presented to the new-world species and 3 subgenera, including Lepyronoxia Melichar, stat.nov. (= Balsana Metcalf, syn.nov.) and Balsania subg.nov. In addition, the tribe contains 15 genera of old-world Aphrophorinae with an estimated 290 species from Pacific islands; of these, the previously undescribed male genitalia from 25 species in 8 genera are illustrated and antennal characters for Orthorapha and 14 Pacific island genera of Orthoraphini are compared to those of Cloviini, Philaenini and Aphrophorini. This is the first tribe of Cercopoidea to be described as limited to the Southern Hemisphere.